The Takrir Method as a Tahfidz Learning Strategy in the Formal Curriculum System of Madrasah Ibtidaiyah - Alfiana Safitri; Firdausih (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2026)
This study examines the application of the takrir method as a tahfidz learning strategy within the formal curriculum system of Madrasah Ibtidaiyah. The study employed a descriptive qualitative approach and was conducted at MI At-Taqwa in Bondowoso. The primary participants included tahfidz teachers, tahfidz homeroom teachers, students, and parents, who served as supporting informants. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. The study’s results revealed four main aspects. First, the tahfidz learning plan is systematically developed through the establishment of phased memorization targets (1 juz per year), integration into the curriculum, and structured time allocation in the morning using the corner mushaf. Second, the implementation of learning emphasizes a balance between memorization review (muroja’ah) and the addition of new memorization through binnadzor and bilghaib activities, as well as individual memorization recitations that begin with the preparation of the Quran and prayer. Third, evaluation is conducted continuously through daily recitations, weekly assessments, pre-munaqosah recitations, as well as mid- and end-of-semester munaqosah as a form of quality control for memorization. Fourth, tahfidz learning is supported by the active role and motivation of teachers, student motivation, parental involvement, and the support of a muroja’ah schedule and audio media, with obstacles including differences in memorization ability, lack of muroja’ah, boredom, the similarity of mutasyabihat verses, and limited learning time. This study concludes that the takrir method contributes to creating structured, consistent, and sustainable tahfidz learning in elementary madrasahs. Theoretically, this study reinforces the importance of repetition-based learning in memorizing the Qur’an. Practically, this study underscores the need for adaptive and well-managed learning strategies in integrating tahfidz into the formal education system.